Influence of Degree of Dispersion of Noncovalent Functionalized Graphene Nanoplatelets on Rheological Behaviour of Aqueous Drilling Fluids - Arif Ibrahim; Syahrir Ridha; Asna Amer; Radzi Shahari; Tarek Ganat (International Journal of Chemical Engineering)
Application of carbon nanomaterials in oil well drilling fluid has been previously studied and was found to enhance its filtration properties. There is a general consensus that addition of colloids in suspension will alter its rheology, i.e., carbon nanomaterials, in this research work; graphene nanoplatelets are hydrophobic materials, which require functionalisation to improve its dispersion in aqueous solution. However, different degrees of dispersion may vary the rheological properties behaviour of drilling fluid. The objective of this study was to characterize the colloidal dispersion of graphene nanoplatelets (GNP) in aqueous solution and its impact on the rheological properties behaviour of water-based drilling fluid. Dispersion of graphene nanoplatelets was achieved through noncovalent functionalisation by means of surfactant attachment. UV-visible spectroscopy was employed to analyze the dispersion of GNP in aqueous solution. The rheological test was carried out using a simple direct-indicating viscometer at six different speeds. Results revealed that the degree of dispersion of GNP using Triton X-100 was generally higher than both SDS and DTAB. Comparison between the rheological properties behaviour of drilling fluid with GNP dispersed using different surfactants shows little to no difference at low shear rates. At high shear rates, however, greater dispersion of GNP shows higher thinning properties while fluid with a low dispersion of GNP exhibited linear behaviour to thickening properties.